Challenging Stereotypes, Lacking Alternatives?: Mapping the Irish Theatre of the Last Twenty Years. Bolger, Dermot, ed. Druids, Dudes and Beauty Queens: The Changing Face of Irish Theatre. Dublin: New Island, 2001. 302 pp. - Pilny, Ondrej (FOCUS: Papers in English Literary and Cultural Studies, 2002)
After Theatre Stuff (edited by Eamonn Jordan, 2000), this is another important collection of essays focused on the variegated nature of contemporary theatre in Ireland in a relatively short time. One of the reasons why Druids, Dudes and Beauty Queens surpasses (never mind its tacky title) its predecessor is that it brings together not only academics and theatre critics but also a large number of theatre practitioners and observers, in order to facilitate different perspectives on the theatre and to cater for all its aspects—literary, practical and social, domestic and international.